Tagging, Pinging and Linking – User Roles in Virtual Citizen Science Forums - Frauke Rohden; Christopher Kullenberg; Niclas Hagen; Dick Kasperowski (Citizen Science: Theory and Practice, 2019)
This article investigates user roles in virtual citizen science projects through a case study of the Talk-forum of Shakespeare’s World, a humanities project on the Zooniverse platform. To address collective knowledge production, we study the use of hashtags, pinging, and linking as a way of differentiating how researchers, moderators, and different user groups use the forum according to their roles. We show how both volunteers and researchers have a much deeper interest in the texts that they transcribe and actively seek contextual information, shape new lines of inquiry, and discover new phenomena. We conclude that the use of online forums in citizen science can play a crucial role for extending the knowledge production from academic research to a wider public interest, and also provide new knowledges beyond the assigned task of transcribing documents.